Cognitive Science of Religion? In the Future Tense? - Jensen, Jeppe Sinding (Journal for the cognitive science of religion, 2019)
Claire White’s introduction to the Cognitive Science of Religion is a valuable research and teaching tool. The uninitiated will truly benefit from the meticulously and clearly formulated expositions of this recent field of research on religion. Although clearly written with students in mind, the volume presents a great opportunity for scholars from other fields to familiarize themselves with the CSR as it has so far been established. A few possible additions and new research avenues are sketched out.